PENGARUH PEMBIAYAAN MURABAHAH, FINANCING TO DEPOSIT RATIO DAN NON PERFORMING FINANCING TERHADAP PROFITABILITAS (Studi pada Bank Syariah di Indonesia Periode 2012 – 2014) - Yusiana Widya A’malina, Suharno & Djoko Kristianto (Universitas Slamet Riyadi, 2016)
purpose of this research is to analyze the significance of the influence of the Murabahah Financing, Financing To Deposit Ratio (FDR) and Non Performing Financing (NPF) partially or simultaneously against profitability at Islamic banks in Indonesia the period 2012-2014. Research methods method using case studies, the data type of the data being used is qualitative and quantitative data, the source data used the data of second. Method of data collection used documentation. Technique of data analysis used a classic assumption test, multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained conclusions: 1) partially known that positive and influential Murabahah Financing significantly to profitability. The bigger the bank financing a Murabahah the greater profitability of the acquired bank. The bank's financial performance improved and increased. 2) partially knowable that Financing To Deposit Ratio (FDR) positive and significant effect against profitability. The results of this research suggest that if FDR is increased which means the bank's profitability increased. 3) partially known that Non Performing Financing (NPF) negative effect is not significantly to profitability. The results of this study demonstrate that NPF bank getting high then so can lower the profitability of the banks concerned, in other words the increase will lower the profitability of the NPF. 4) simultaneously can note that financing the Murabahah, Financing To Deposit Ratio (FDR) and Non Performing Financing (NPF) effect significantly to profitability. This means the management can pay attention to financing the Murabahah, Financing To Deposit Ratio (FDR) and Non Performing Financing (NPF) with the aim of improving the bank's financial performance to always fall into the category of healthy banks so that the public and investors choose to do banking transactions and invested in the bank.Keywords: murabahah financing, FDR, NPF, profitability